Salvage of a fifteen days old thrombosed dialysis fistula: A case report - Saxena, Agamya; Mishra, Padma (Indian Journal of Case Reports, 2019)
Hemodialysis fistulae are important conduits for successful long-term dialysis in chronic kidney disease patients. More often than not, these fistulae are prone to get thrombosed or stenosed, especially at the juxta-anastomotic sites. The venous outflow is a commoner site, as rapid arterial inflow leads to a higher incidence of neointimal hyperplasia. Early signs of stenosis or thrombosis are easy to detect viz. decrease/loss of thrill, slow hemodialysis filtration rate resulting in unusually longer time spans for a dialysis session or inadequate dialysis overall. Early detection can help planning an early radiological intervention in the form of thromboaspiration, thrombolysis, balloon angioplasty or stenting. However, the older a thrombus, the harder it is to get rid of. We present here a case of fifteen days old thrombosis of a radio-cephalic fistula, which underwent thromboaspiration and balloon angioplasty, with a satisfactory result. Dialysis fistula is the “life-line” of chronic kidney disease patients; and in line with the “fistula first” initiative, our case exemplifies its motto.